Bias Media Mengenai Pemberitaan Batalnya Indonesia Menjadi Tuan Rumah Piala Dunia U-20 2023 di Media Online tirto.id dan tempo.co - Lambe, Pearly Claire Christabella; Saputro, Nugroho Piter; Hidayat, Elguarddine; Charoline, Elisabeth; Wulan, Roro Retno (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research discusses the bias of the news media regarding Indonesia's cancellation of hosting the 2023 U-20 World Cup. One of the causes is the rejection of the participation and presence of the Israel national team in Indonesia. Apart from being sanctioned by FIFA, the cancellation of hosting the U-20 World Cup will have a major impact on Indonesia. Because the World Cup benefits the country appointed by the President of FIFA to host it. Many media outlets have reported on the cancellation of Indonesia as the host for the 2023 U-20 World Cup, such as Tirto. id and tempo. co. This research is descriptive research with qualitative methods and uses Discourse Network Analysis (DNA) to analyze the data. Based on the news that has been collected, a total of 35 actors participated and were involved in the issue of the failure of the U-20 world cup in Indonesia and there is no partiality between the two online media on one side.